2022
DOI: 10.1111/nbu.12549
|View full text |Cite
|
Sign up to set email alerts
|

Can sprouting reduce phytate and improve the nutritional composition and nutrient bioaccessibility in cereals and legumes?

Abstract: Sprouting is a traditional processing method which has been used for centuries to improve the nutritional value of cereals and legumes. There has been growing interest in sprouted products in recent years due to a high demand for more natural and healthy foods. Phytate is the primary storage form of phosphorus in plants. It is long recognised to affect human health as it forms insoluble complexes with minerals such as iron and zinc in cereals and legumes, thereby preventing their absorption in the body. Sprout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…Similar and slightly reduced PA content was observed for OPM1 and OPM2, respectively, as compared to that of the control. This effect could result from sprouting, which activates endogenous phytase [ 65 ]. As for GABA and TSPC, the optimized extrudates were better sources of these bioactive compounds with levels between five and eight times higher as compared to those of the control extrudates.…”
Section: Resultsmentioning
confidence: 99%
“…Similar and slightly reduced PA content was observed for OPM1 and OPM2, respectively, as compared to that of the control. This effect could result from sprouting, which activates endogenous phytase [ 65 ]. As for GABA and TSPC, the optimized extrudates were better sources of these bioactive compounds with levels between five and eight times higher as compared to those of the control extrudates.…”
Section: Resultsmentioning
confidence: 99%
“…It needs to be noted that many factors can play a role in this process. For instance, optimal phytate degradation is 38-55 °C at a pH of 4.5-8 in legumes (Elliott et al 2022), while maximum phytase activity in chickpeas was observed 6-8 days after germination (Kyriakidis et al 1998).…”
Section: Effects Of Sprouting Conditions On Germination Physiology La...mentioning
confidence: 99%
“…Sprouting is also alternatively known as malting because this process has been used for centuries to produce malts with distinctive functionality and flavors for the brewing and distilling industry. The growing interest in this method in recent years is due to a high demand for more natural and healthy foods [77]. Sprouting can induce changes in the nutritional composition through enzymatic hydrolysis of existing compounds and de novo synthesis of new compounds [78].…”
Section: The Influence Of Germination On β-D-glucans In Cerealsmentioning
confidence: 99%